FATIGUE LIFE ANALYSIS OF TRANSMISSION SHAFT BASED ON TESTING LOAD - LIU DiHui; ZHU Rui; HE Yao (Jixie qiangdu)
Aimed at fracture of transmission shaft about some kind of transport for bulk dry-mixed mortar,this paper designed a set of testing equipment which can test torque,run out,revolving speed. This testing equipment provides with analyzed data on fault diagnosis and maintenance of this kind of brand new car. This set of testing equipment was also applied to the fault diagnosis of concrete pump truck and mix concrete truck. The place where the fracture of transmission taken place is very complex and it is very difficult to do the stress measurement of the hot spot of fracture taken place. This paper converted the measure data of torque into the stress of the hot spot of fatigue by using the FEA. Calculating the fatigue life of shaft by combining the structural S-N curve and the modified Miner’s rule were carried out. This method can provide a way of calculating fatigue life of shaft of engineering machine.